The Poor, the Rich and the Enforcer: Institutional Choice and Growth - Thor Koeppl; Cyril Monnet; Erwan Quintin (Queen's University, Department of Economics, 2007)
We study economies where improving the quality of institutions - modeled as improving contract enforcement - requires resources, but enables trade that raises output by reducing the dispersion of marginal products of capital. We find that in this type of environment it is optimal to combine institutional building with endowment redistribution, and that more ex-ante dispersion in marginal products increases the incentives to invest in enforcement. In addition, we show that institutional investments lead over time to a progressive reduction in inequality. Finally, the framework we describe enables us to formalize the hypothesis formulated by Engerman and Sokoloff (2002) that the initial concentration of human and physical capital can explain the divergence of different countries' institutional history.
Keywords: D31; D52; O11; O43; 330; Enforcement as a Choice; Institutions; Inequality; Human and Physical Capital; Institutionenökonomik; Vertragstheorie; Wirtschaftswachstum; Kapitalproduktivität; Soziale Ungleichheit; Institutioneller Wandel; Theorie